2014
DOI: 10.7600/jpfsm.3.525
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar intervertebral disc degeneration in collegiate rowers

Abstract: The aim of this study was to clarify the prevalence and distribution of disc degeneration in collegiate rowers and investigate the relationship between disc degeneration progression and low back pain (LBP). In this cross-sectional study, 68 collegiate rowers were evaluated for lumbar disc degeneration using the Pfirrmann classification based on T2-weighted magnetic resonance imaging (MRI). After 2 years, 20 participants underwent follow-up MRI. Injury surveillance to check LBP was conducted between the first e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Based on the MRI studies ( Tertti et al, 1990 ; Baranto et al, 2006 ; Kaneoka et al, 2007 ; Kraft et al, 2009 ; Koyama et al, 2013 ; Sekine et al, 2014 ; Thoreson et al, 2017b ; Witwit et al, 2018 ), the most common abnormalities in athletes of individual sports were as follows: reduced disc signal, degenerated discs at various disc levels, ring apophyses injury, disc bulging, Schmorl’s nodes causing severe back pain, abnormal configuration of the vertebra, and alterations in spinal curvatures.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the MRI studies ( Tertti et al, 1990 ; Baranto et al, 2006 ; Kaneoka et al, 2007 ; Kraft et al, 2009 ; Koyama et al, 2013 ; Sekine et al, 2014 ; Thoreson et al, 2017b ; Witwit et al, 2018 ), the most common abnormalities in athletes of individual sports were as follows: reduced disc signal, degenerated discs at various disc levels, ring apophyses injury, disc bulging, Schmorl’s nodes causing severe back pain, abnormal configuration of the vertebra, and alterations in spinal curvatures.…”
Section: Resultsmentioning
confidence: 99%
“…It confirms the biological, and physiological, nature of cyclic compression for nuclear health. If in fact, the disc was truly adapting we would likely NOT see an overwhelming amount of research showing an extremely high prevalence of disc degeneration in rowers [19][20][21]. In fact, it is important to consider that the authors themselves said, "intensive athletic exercise at a professional level is associated with early degenerative changes, including disc herniation.…”
Section: Gag Content + Ivd Adaptationmentioning
confidence: 99%
“…In addition, signs of disc degeneration are associated with LBP [ 13 ]. A longitudinal study that investigated the relationship between LBP and intervertebral disc degeneration in collegiate rowers also reported that lumbar intervertebral disc degeneration is related to LBP [ 14 ]. Therefore, in this study, we focused on lumbar intervertebral disc degeneration associated with LBP in rowers.…”
Section: Introductionmentioning
confidence: 99%